Iron age metal working at the Tsodilo Hills, Northwestern Botswana - Miller, Duncan (Department of Archaeology, 2016)
This study documents the metal working technology employed at two major Iron Age archaeological sites in southern Africa. The research involved the description and analysis of two large metal working assemblages with a total of 2922 metal artefacts, fragments of ore, and slag, from the sites of Divuyu (6th 8th century AD) and Nqoma (7th - 10th century AD, with a later 17th - 19th century AD occupation) in the Tsodilo Hills, northwestern Botswana. This is the first systematic description and metallographic analysis of a large collection of Early Iron Age metal artefacts from southern Africa. The artefacts were small, mainly delicate items of copper and iron jewellery, and tools possibly used in their manufacture. They were classified, described, and sampled selectively for metallographic, petrographic, and chemical analysis. Seventy artefacts were studied in detail, from which the fabrication technology employed at these sites was reconstructed. During the Early Iron Age forging, and probably also smelting, of iron took place at both sites. The smelting products were inhomogeneous iron and steel, with typical fayalitic slag, characteristic of indigenous bloomery iron production. The forging was done in an oxidising hearth and the technique used was poor, with no deliberate control over carbon content, the mechanical properties of the steel, or heat treatment other than annealing. Fabrication involved hammering square wire and flat sheets, which were cut into strips for beads, clips, chains, and fibre-cored wound ornaments. Numerous finger rings were made from crude round iron wire. Copper was worked in the same way, generally leaving the metal in its annealed state. Significant chemical variation in the copper artefacts and iron slag inclusions indicated that diverse ore sources were involved. There were stylistic similarities between individual artefacts from the Tsodilo Hills and Early Iron Age material from the Upemba Depression in Zaire, as well as with a copper chain from Broederstroom in the Transvaal. Comparison of the fabrication technology with Later Iron Age material suggested that local indigenous iron and copper working technology has changed little since its introduction in southern Africa.